Increasing Independence in Providing Feed in Tilapia Cultivation in Gapokkan Tilapia Village, Kawali District, Ciamis Regency - Candra Nuraini; Ati Rosliyati; Erviyana Windiastuti; Lidya Nur Amalia; betty rofatin; Octaviana Helbawanti (Universitas Veteran Bangun Nusantara, 2026)
ABSTRACT The fishing industry plays an important role in national food security and community economic improvement. Ciamis Regency, through Kampung Nila in Kawali District, has been designated as a center for tilapia (Oreochromis niloticus) farming. This commodity was chosen because of its rapid growth, affordable price, and stable market demand. However, farmers face high production costs due to their dependence on commercial feed, which reduces their profits. This community service program aims to increase farmers' independence through innovation in self-sufficient feed based on local materials. The method used is Participatory Rural Appraisal (PRA) with stages of socialization, training, Keywords: Nila Village, Management, Feed Milling Machines, Empowerment, Appropriate Technology.